Physical fights involvement in school setting and adolescents’ behaviours : highlights from health behaviour in school-aged children (HBSC/WHO) - fights in school setting and adolescent’s behaviours - Gaspar, Susana (2019)
Copyright © 2019 Susana Gaspar et al. This is an open access article distributed under the Creative Commons Attribution License which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and work is properly cited.